Mushroom - Money, Nicholas P. (New York : Oxford University Press, 2011)
An illuminating look at the wonders of mushroom biology and an exploration of their enduring appeal. Nicholas Money leads readers through a history of mushroom research, painting portraits of the colourful characters involved in their study.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mushrooms